Einsatz der Standards von IMS Global Learning Consortium bei der Erstellung der Lehrmaterialien für Sprachkurse: Einschränkungen und Lösungen - Tiutenko, Arthur (Fremdsprachenlernen online. Erfahrungen und Erkenntnisse im Projektverbund SprachChancen, 2007)
The following article reports on practical experience in the usage of the Question and Test Interoperability Specification of the IMS Global Learning Consortium for the production of language courses. The many problems that both the authors of learning content and software developers encounter in striving to implement the standard need to be solved with as little negative effect as possible on the quality of the learning materials. Given that it is not always possible to maintain confor- mance with a standard, it is, arguably, not the standards as such that are impor- tant, but rather the abandonment of binary data storage and the usage of open, XML-based formats.
Keywords: E-Learning